Locational decisions of educated family members in Finland - Taru Järvinen (European Regional Science Association (ERSA), 2002)
The process of concentration of human capital is clearly reinforced by inter-regional migration in Finland. The spatial mismatch between positions and skilled labour force is increasing and the concentration of human capital can easily be seen in the distribution of dual career families home locations that favors few growing city areas. At the individual level job access is the result of the location of the residence in relation to locations of employment opportunities and the commuting tolerance of individuals. Personal unemployment and commuting experiences of men and women effects differently to the propensity of family migration. Wives do have power equally with men in the decision making processes of families but still the career of men seems to be prioriced. The paper examines the relocation process, in relation between residential relocation and commuting distance, in families where both partners are classified as the holders of specialist careers. Job and residential search behaviour are analysed at the local labour market area level based to the query data. The purpose is to determine the locational factors that have the most importance while combining the family and working lives. The family location is analysed in relation to the native places of women and men, cumulative work opportunities, educational levels and family life cycle eras.
Keywords: 330